2014
DOI: 10.1016/j.jcrs.2014.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Sutured posterior chamber intraocular lenses for traumatic cataract in Africa

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…In our results, 18.1% received combined cataract and antiglaucoma surgery. Similar to Rogers et al's report [20], 28% of the patients had hypertension complications after traumatic cataract.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our results, 18.1% received combined cataract and antiglaucoma surgery. Similar to Rogers et al's report [20], 28% of the patients had hypertension complications after traumatic cataract.…”
Section: Discussionsupporting
confidence: 86%
“…Serna-Ojeda et al reported that 58.7% of cases obtained VA ≥ 20/40 [16]. Rogers et al reported 66.7% of cases obtained VA of >20/60 [20]. Memon et al reported that 70.8% of cases obtained VA of >20/60 [17].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms may be involved in the development of elevated IOP after ocular trauma, such as injury to trabecular meshwork, hyphemia, injury to the lens and/or iris, inflammation, peripheral anterior synechiae, vitreous hemorrhage, angle recession and topical corticosteroid use [39]. In cases of angle recession and coexisting lens subluxation, there may be an increased risk for secondary glaucoma [40]. [41].…”
Section: Discussionmentioning
confidence: 99%
“…Gradin ve Yorston bu oranı %64,7, Rogers ve ark. %66,7, Shah ve ark %54,3 olarak bildirmiştir [10][11][12]. Ülkemizde yapılan Yeter ve Güngör'ün yaptığı 16 olgudan oluşan bir çalışmada ortalama 1.ay EİDGK 0,49; 20/40 ve üzerinde görme oranına sahip olanların oranı ise %57 olarak bildirilmiştir [13].…”
Section: Discussionunclassified